The Frequency of Common Complications of Veress Needle in Laparoscopic Cholecystectomy - Rahman, Faiz -Ur-; Junaid, Fazli; Khattak, Bilal; Shah, Azhar; Amin, Arshad (Journal of Gandhara Medical and Dental Science, 2017)
METHODOLOGY The study was conducted in department of surgery, Lady Reading Hospital Peshawar within six months and it was descriptive cross sectional study. In this study a total of 177 patients were observed. The age ranges were 21 to 65 years and male to female ratio was 1:2. The most common complication was abdominal wall hemorrhage in 22% patients while 18% patients had omental injury. The abdominal wall emphysema was observed in 10% patients. OBJECTIVE To determine the frequency of common complications of Veress Needle used for creating pneumoperitoneum in laparoscopic cholecystectomy CONCLUSION Our study showed that veress needle technique is safe, easy and cost effective for primary access to create pneumoperitonium.